The patchwork bike - Clarke, Maxine Beneba (Candlewick Press, 2018)
"When you live at the edge of the no-go desert, you need to make your own fun. That's when you and your brothers get inventive and build a bike from scratch, using everyday items like an old milk pot (maybe Mum is using it, maybe not), a bent bucket seat, and bashed tin-can handles. The end result is a spectacular bike, perfect for going bumpetty bump over the sand hills, past your fed-up mum, and right through your mud-for-walls home."--Back cover.